Gastrodin attenuates vincristine-induced mechanical hyperalgesia through serotonin 5-HT1A receptors - Guo, Zheng-Gang; Jia, Xiao-Pen; Su, Xiao-Jun; Li, Ping; Hao, Jian-Hua (Bangladesh Journal of Pharmacology, 2013)
Gastrodia elata Blume (Orchidaceae) is an old traditional Chinese medicine with demonstrated analgesic efficacy in humans. However, the potential analgesic effect of its active component, gastrodin, has not been systematically studied. This work described the anti-hyperalgesic effect of gastrodin in a mouse model of chemotherapeutic agent vincristine-induced neuropathic pain. Gastrodin (0.05-0.8 mg/kg) dose-dependently reverted the mechanical hyperalgesia in mice. In addition, the anti-hyperalgesic effect of gastrodin was significantly blocked by a selective serotonin 5-HT1A receptor antagonist WAY100635 (1 mg/kg). In contrast, gastrodin did not significantly alter the general locomotor activity in mice. Taken together, this study demonstrated that gastrodin possesses robust analgesic efficacy in mice and may be a novel analgesic for the management of neuropathic pain.